Pengaruh Media Pembelajaran Berbasis Flipbook terhadap Hasil Belajar IPAS Siswa SD Negeri 162 Palembang - Mutiana Mutiana; Lukman Hakim; Agung Mahendra (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aimed to determine the effect of flipbook-based learning media on students’ learning outcomes in Science and Social Studies (IPAS) on the topic of energy transformation for fourth-grade students at SD Negeri 162 Palembang. The background of this study was based on students' low learning outcomes, limited participation during the learning process, and the suboptimal use of digital learning media in the classroom. This research employed a quantitative approach using a quasi-experimental method with a Nonequivalent Control Group Design. The population consisted of 42 fourth-grade students, with Class IV.A serving as the experimental group and Class IV.B as the control group. The sampling technique used was total sampling. Data were collected through pretests and posttests and analyzed using normality tests, homogeneity tests, and hypothesis testing through an Independent Sample t-test. The results showed that the average posttest score of the experimental class was 81.4, while the control class achieved an average score of 53. The hypothesis testing result indicated a significance value (Sig. 2-tailed) of 0.000 < 0.05, meaning that H₀ was rejected and Hₐ was accepted. Therefore, it can be concluded that the use of flipbook-based learning media has a significant effect on students' learning outcomes in IPAS on the topic of energy transformation among fourth-grade students at SD Negeri 162 Palembang. The flipbook-based learning media was proven to enhance conceptual understanding, learning motivation, and student participation during the learning process.